Rancang Bangun Turbin Angin Untuk Pembangkit Listrik Hybrid One Pole Energy - Roswati Nurhasanah (Sekolah Tinggi Teknik - PLN, 2020)
Wind energy can be utilized by the potential of electricity by using a wind turbine, so that the electricity raised power is greater than can be combined with the type of solar energy source. So that it can back up each other if the weather is uncertain. HOPE (Hybrid One Pole Energy) is a Hybrid power plant that is designed to exploit the potential of wind and solar energy in the campus area of PLN Jakarta Institute of Technology, from the measurement results obtained that the average wind speed is 3.5 m/s. Wind turbine designed type of wind turbine Horizontal axis, airfoil NACA 4412 type tapperless with the number of Blades 3. Data processing and simulation are done using Qblade v. 0963 software with a maximum wind speed of 12 m/s. The Material used to make this turbine blade is of teak wood. The results of the turbines of a turbine tapperless with 10 segmen, R=0,9 m α = 6o, Cl = 1.63, Cl/Cd = 133,6 and Cr = 0.18 m and Cp = 42%. From the test results acquired average power that can be raised by 25, 1W while HOPE can optimize the raised power of the average reaches 54.7 W.